Successful recovery from COVID-19 pneumonia after receiving baricitinib, tocilizumab, and remdesivir. A case report: Review of treatments and clinical role of computed tomography analysis. (2020) - Sodani, Pietro; Mucci, Luciano; Girolimetti, Rita; Tedesco, Silvia; Monaco, Francesca; Campanozzi, Daniele; Brunori, Marino; Maltoni, Stefania; Bedetta, Samuele; Di Carlo, Anna M.; Candoli, Piero; Mancini, Mauro; et al.
Abstract: The novel coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a pandemic, threatening global public health. In the current paper, we describe our successful treatment of one COVID-19 pneumonia patient case with high mortality risk factors. Our experience underlines the importance of the use of a multidisciplinary therapeutic approach in order to achieve a favorable clinical outcome. Further, enhancing the capability of the COVID-19 diagnosis with the use of the chest imaging modalities is discussed.